Optimization of Culture Conditions for Secretory Production of 3-Hydroxybutyrate Oligomers Using Recombinant Escherichia coli - Sakurai, Tetsuo; Mizuno, Shoji; Miyahara, Yuki; Hiroe, Ayaka; Taguchi, Seiichi; Tsuge, Takeharu (Frontiers in Bioengineering and Biotechnology, 2022)
Poly(3-hydroxybutyrate) [P(3HB)] is the most representative polyhydroxyalkanoate (PHA), which is a storage polyester for prokaryotic cells. P(3HB)-producing recombinant Escherichia coli secretes diethylene glycol (DEG)-terminated 3HB oligomers (3HBO-DEG) through a PHA synthase-mediated chain transfer and alcoholysis reactions with externally added DEG. The purpose of this study was to optimize the culture conditions for the secretory production of 3HBO-DEG with jar fermenters. First, the effects of culture conditions, such as agitation speed, culture temperature, culture pH, and medium composition on 3HBO-DEG production, were investigated in a batch culture using 250-mL mini jar fermenters. Based on the best culture conditions, a fed-batch culture was conducted by feeding glucose to further increase the 3HBO-DEG titer. Consequently, the optimized culture conditions were reproduced using a 2-L jar fermenter. This study successfully demonstrates a high titer of 3HBO-DEG, up to 34.8 g/L, by optimizing the culture conditions, showing the feasibility of a new synthetic strategy for PHA-based materials by combining secretory oligomer production and subsequent chemical reaction.